2005
DOI: 10.1021/jf050923j
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, Structural, Thermal, and Rheological Characteristics of Starches Separated from Apples of Different Cultivars

Abstract: The starches were separated from unripe apples of five cultivars (Criterion, Ruspippum, Red Spur, Skyline Supreme, and Granny Smith) and evaluated using scanning electron microscopy (SEM), gel permeation chromatography (GPC), X-ray diffraction, differential scanning calorimetry (DSC), and dynamic viscoelasticity. SEM showed the presence of round granules as well as granules that had been partially degraded, probably by amylases. The starch granules in different apple starches ranged between 4.1 and 12.0 mum. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 39 publications
2
11
0
1
Order By: Relevance
“…At temperatures between 90 and 70 °C, traces of G′ and G″ remained relatively flat, consistent with what has been reported for cultivars of rice and apple [28]. All samples of malted sorghum exhibited low peaks in shear modulus, in contrast, the corresponding traces for RG and 24hSG were relatively steep forming a sigmoidal pattern of modulus development.…”
Section: Resultssupporting
confidence: 87%
“…At temperatures between 90 and 70 °C, traces of G′ and G″ remained relatively flat, consistent with what has been reported for cultivars of rice and apple [28]. All samples of malted sorghum exhibited low peaks in shear modulus, in contrast, the corresponding traces for RG and 24hSG were relatively steep forming a sigmoidal pattern of modulus development.…”
Section: Resultssupporting
confidence: 87%
“…The shorter average amylopectin branch chain lengths observed for pin-milled oat starch compared with starch from entire kernels, corroborates analysis of amylopectin density that pin-milling may degrade exterior chains that have longer polymerization. Presence of long side chains in amylopectin have been reported (Reddy et al 1993;Takeda et al 1993Takeda et al , 1999Singh et al 2005), although Matheson (1996) found amylopectin density can increase by lengthening ci-glucan chains in the external, internal, or core molecular regions. Repeated, lengthy ball-milling of the wheat starch converted some amylopectin to low molecular weight fragments that were derived from shearing glycosidic bonds in the long 132, 133, and 134 internal chains (Morrison and Tester 1994).…”
Section: Amylopectin Branch Chain Length Distributionmentioning
confidence: 98%
“…Size distributions of the starch granules were estimated by classifying the size of starch granules into four groups: large (>25 µm), medium (10-25 µm), small (5-10 µm) and very small (<5 µm). 14 Reducing capacity, iodine absorption spectra and blue value The starch samples for the determination of reducing capacity were prepared according to the method of Singh et al 15 and the reducing capacity of the starch samples was determined (as glucose equivalent) using the modified Park and Johnson method. 16 Iodine spectra of the native starches were determined following the dimethyl sulfoxide-urea method 17 and the blue value (BV) was measured as absorbance at 680 nm.…”
Section: Granular Morphologymentioning
confidence: 99%